James Jesse Strang: the rise and fall of Michigan's Mormon king - Faber, Don (University of Michigan Press, 2016)
James Strang's America -- Formative years -- The diary -- Pivotal meeting : James Strang and Joseph Smith Jr -- The succession crisis -- Strang makes his move -- Arrival on Beaver Island -- Mormons vs. gentiles -- Polygamy : Strang's reversal -- His Majesty, King James -- The king on trial -- The honorable James Strang -- Pine River -- Assassination -- Aftermath -- A man of settled purpose